2007
DOI: 10.2337/dc06-2057
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance Is Associated With Hypercortisolemia in Polynesian Patients Treated With Antipsychotic Medication

Abstract: OBJECTIVE -Type 2 diabetes is more prevalent in the indigenous Polynesian population of New Zealand (Maori) than in Europeans. The aim of this study was to determine whether insulin resistance in Maori psychiatric patients was associated with antipsychotic treatment and to investigate the mechanism of an association.RESEARCH DESIGN AND METHODS -Thirty adult Maori psychiatric patients receiving antipsychotic medication for Ͼ6 months and 30 healthy, age-, sex-, and BMI-matched control subjects were enrolled. Ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…Hypercortisolism is apparently characterized by impaired insulin-dependent glucose uptake in the periphery and enhanced gluconeogenesis in the liver [12,13]. Although propranolol treatment suppressed cortisol secretion in the present case, glucose metabolism did not improve.…”
Section: Discussioncontrasting
confidence: 58%
“…Hypercortisolism is apparently characterized by impaired insulin-dependent glucose uptake in the periphery and enhanced gluconeogenesis in the liver [12,13]. Although propranolol treatment suppressed cortisol secretion in the present case, glucose metabolism did not improve.…”
Section: Discussioncontrasting
confidence: 58%
“…[68][69][70] Our report is the first known study comparing hair cortisol content of 2 distinct cultural groups. [68][69][70] Our report is the first known study comparing hair cortisol content of 2 distinct cultural groups.…”
Section: Discussionmentioning
confidence: 86%
“…Psychosis is prevalent in bipolar disorder and schizophrenia, as well as in dementia, major depressive disorder and few personality disorders. 1 In Pakistan recently there has been a rise in the use of antipsychotics, particularly atypical antipsychotics, with little polypharmacy. The overall use of antipsychotics increased by 4.3 fold in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…This partially occurs through central nervous system and result in impaired insulin action through brain. 3 Unfortunately, several studies have linked the patient on antipsychotic treatment with the occurrence of insulin resistance, impaired glucose tolerance and type 2 diabetes 1,4,5 but the cause behind this correlation is not established. Research suggested that schizophrenia patients had higher diabetes levels than the normal population.…”
Section: Introductionmentioning
confidence: 99%